2020
DOI: 10.1111/jon.12760
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index Correlates with Skin to Spinal Canal Distance: A Large Retrospective Single‐Center Study

Abstract: BACKGROUND AND PURPOSE: Despite increasing demand for fluoroscopy-guided lumbar puncture (FG-LP), there is limited quantitative and epidemiological data on patients undergoing this procedure. Additionally, data are scarce on the correlation of iliac crest landmarks to the actual anatomical lumbar level (intercristal line). The aim of this study is to determine if (1) body mass index (BMI) correlates with skin to spinal canal distance (SCD) and (2) the iliac crest landmark correlates with the presumed anatomica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Mahmoudi et al . [ 6 ] reported that the distance between the skin and the spinal canal, between the 3 rd and 4 th , 4 th and 5 th lumbar vertebrae, and 5 th lumbar vertebrae and 1 st sacral vertebrae is proportional to BMI and increases as it goes caudally. In our case, Figure 3 shows that the distance between the lumbar vertebrae and the skin increased caudally which suggests that the lumbar vertebrae and the skin are not parallel when the patient is seen from the side, but oblique caudally and spreads out [ Figure 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mahmoudi et al . [ 6 ] reported that the distance between the skin and the spinal canal, between the 3 rd and 4 th , 4 th and 5 th lumbar vertebrae, and 5 th lumbar vertebrae and 1 st sacral vertebrae is proportional to BMI and increases as it goes caudally. In our case, Figure 3 shows that the distance between the lumbar vertebrae and the skin increased caudally which suggests that the lumbar vertebrae and the skin are not parallel when the patient is seen from the side, but oblique caudally and spreads out [ Figure 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…31,52 Standard-length needles (70-90 mm) are used in adults, although longer needles may be needed in obese patients. 53,54 The use of longer needles makes the procedure more difficult because such needles are more flexible and thus have a tendency to divert off track. 31,55 This may necessitate multiple attempts at LP, causing local swelling, bruising, or muscle spasms, and increasing the risk of back pain.…”
Section: Boxmentioning
confidence: 99%
“…Standard‐length needles (70–90 mm) are used in adults, although longer needles may be needed in obese patients 53,54 . The use of longer needles makes the procedure more difficult because such needles are more flexible and thus have a tendency to divert off track 31,55 .…”
Section: Recommendations For Reducing the Risk Of Post‐lp Adverse Eventsmentioning
confidence: 99%